2003
DOI: 10.1007/s00268-003-6976-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Breast Cancer in Malaysian Women: Overview

Abstract: Breast cancer is the most common cancer among Malaysian women. Nonetheless, in Malaysia there is a marked geographical difference in the incidence of breast cancer with advanced stage of presentation. The breast clinic in Kuala Lumpur Hospital diagnosed approximately 150 to 200 new cases of breast cancer a year. This number, however, represents only 12.0% to 15.0% of all breast disease seen annually in Kuala Lumpur Hospital. Between 1998 and 2001, of a total of 774 cases of newly diagnosed breast cancer in Kua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 10 publications
11
68
0
1
Order By: Relevance
“…The results of some studies carried out in Korea (Lee et al, 2000;Im, et al, 2004), Singapore (Straughn and Seow, 2000) Malaysia (Hisham and Yip, 2003), Iran (Jarvandi et al, 2002) showed that not only the women did not perceive the importance of early detection of breast cancer, but also they had inadequate knowledge on breast cancer and screening test.…”
Section: 969 Predictors Of Mammography Screening Among Iranian Womenmentioning
confidence: 99%
“…The results of some studies carried out in Korea (Lee et al, 2000;Im, et al, 2004), Singapore (Straughn and Seow, 2000) Malaysia (Hisham and Yip, 2003), Iran (Jarvandi et al, 2002) showed that not only the women did not perceive the importance of early detection of breast cancer, but also they had inadequate knowledge on breast cancer and screening test.…”
Section: 969 Predictors Of Mammography Screening Among Iranian Womenmentioning
confidence: 99%
“…Cultural and social perceptions of breast cancer are the most important factors in the presentation of breast cancer at the advanced stage among Malaysian breast cancer patients (Hisham and Yip, 2003). Breast cancer not only threatens the life of a woman but also effects her body image and gender identity (Parsa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The univariate analysis done in this study encountered that the risk factors within Gail Model have no significant correlation with different mammography findings in this subjects groups which is relatively similar with the finding in a study within Indian subjects (Challa et al, 2013). Despite that, as the Gail Model had been validated in several studies to be able to predict individual risk in contracting breast cancer, we find it will be very beneficial to use the key risks pointed out by the model as our covariates and cofactors (Hisham and Yip, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Until to date the best prevention program in Malaysia to fight breast cancer is still depending on breast selfexamination and annual mammography screening after the age of 40 years old (Hisham and Yip, 2003). The fact that mammography procedure involves exposure to X-ray radiation limits the age group of screening and painful compression had made this procedure less popular in our population (Dahlui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%